Spiritual growth and care in the fourth age of life - MacKinlay, Elizabeth, 1940- (Jessica Kingsley Publishers, 2006)
Spiritual Growth and Care in the Fourth Age of Life explores the spiritual dimension of ageing and investigates the role of pastoral and spiritual care in helping the frail elderly cope with end-of-life issues. Focusing on the experience of nursing home residents and anecdotes gathered in interviews, MacKinlay sensitively presents the struggles facing older people in need of care, such as loss of independence and privacy. Her findings show that despite ill health, loneliness and depression, older people near the end of their lives find meaning and support in (re)discovering their spirituality, and that this is not just the experience of those in care facilities, but of older people more generally. The book includes a useful chapter on spiritual assessment, providing carers with information on how to recognise the need for care. This book will be of interest to nurses, care workers, pastoral support professionals and anyone else working with older people.